Respuesta :

Answer:

x = -6

Step-by-step explanation:

x^2 +12x +36=0

What 2 numbers multiply to 36 and add to 12

6*6 = 36

6+6 = 12

(x+6) (x+6) = 0

Using the zero product property

x+6 = 0  x+6 =0

x=-6   x=-6

Since they are the same we only list the solution once

Answer:

[tex]-6[/tex]

Step-by-step explanation;

[tex]x^{2} +12x+36=0[/tex]

Comparing with ax² +bx² + c=0

where a =1 , b=12, and c= 36

[tex]x_{1,\:2}=\frac{-b\pm \sqrt{b^2-4ac}}{2a}[/tex]

substituting the values of a, b, and c to find the value of x

[tex]x=\frac{-12\pm \sqrt{12^2-4\cdot \:1\cdot \:36}}{2\cdot \:1}[/tex]

[tex]x=\frac{-12+,-\sqrt{144-144} }{2}[/tex]

[tex]x=\frac{-12+,-0}{2} =-6[/tex]

OAmalOHopeO